Decoding Argentina's path to World Cup glory: Unveiling the winning factors in match result analysis - Yudibaskara, Gabriel Possenti Angga; Ria, Lumintuarso; Tomoliyus; Perdana, Glady (UIR Press, 2023)
The use of technology in evaluating the results of football matches has been used in various countries. This study aimed to identify and analyze the match results of the Argentina national team as the 2022 World Cup champion team. This research was a descriptive quantitative research that was analyzed in statistical form. The data sources were collected by the researcher by analyzing statistical data and video recordings of matches from the official FIFA website, Whoscored and Vidio. A total of 7 matches had been played by the Argentina national team in the 2022 World Cup competition, analyzed in terms of goals, ball possession, attempts at goal, direction of attack, distribution and defense. The results showed that most goals were scored in the 31-45th minute and most conceded in the 76-90 th minute, with the most ways being open play, most goals scored in area 3 with the striker being the top scorer. Argentina is quite dominant and controls the match in ball possession, attempt on target and total distribution (passing success, crossing success, and line breaks success) in every match with many attacks started from the right. When carrying out defensive pressure and tackles, Argentina is also more effective than its opponent. In this study, it could be concluded that the parameters to achieve victory were not only from ball possession, attempt success, and passing success but also seen from distribution parameters (crossing and line break success) and defensive parameters, especially defensive pressure which was also an indicator of team success in a match. It is hoped that in the future there will be further research discussing the successful journey of a team in several competitions followed by analysis parameters that are not much different, especially with a more detailed analysis of distribution and defense systems.